Disparities in ethnicity and metabolic disease burden in referrals to nephrology - Yan Ting Chua; Cheang Han Leo; Horng Ruey Chua; Weng Kin Wong; Gek Cher Chan; Anantharaman Vathsala; Ye Lu Mavis Gan; Boon Wee Teo (Singapore Medical Journal)
Introduction: The profile of patients referred from primary to tertiary nephrology care is unclear. Ethnic Malay patients have the highest incidence and prevalence of kidney failure in Singapore. We hypothesised that there is a Malay predominance among patients referred to nephrology due to a higher burden of metabolic disease in this ethnic group. Methods: This is a retrospective observational cohort study. From 2014 to 2018, a coordinator and physician triaged patients referred from primary care, and determined co-management and assignment to nephrology clinics. Key disease parameters were collated on triage and analysed. Results: A total of 6,017 patients were studied. The mean age of patients was 64 ± 16 years. They comprised 57% men; 67% were Chinese and 22% were Malay. The proportion of Malay patients is higher than the proportion of Malays in the general population (13.4%) and they were more likely than other ethnicities to have ≥3 comorbidities, including diabetes mellitus, hypertension, hyperlipidaemia, coronary artery disease and stroke (70% vs. 57%, P < 0.001). Malay and Indian patients had poorer control of diabetes mellitus compared to other ethnicities (glycated haemoglobin 7.8% vs. 7.4%, P < 0.001). Higher proportion of Malay patients compared to other ethnicities had worse kidney function with estimated glomerular filtration rate (eGFR) <30 mL/min/1.73 m2 on presentation (28% vs. 24%, P = 0.003). More ethnic Malay, Indian and younger patients missed appointments. Conclusion: A disproportionately large number of Malay patients are referred for kidney disease. These patients have higher metabolic disease burden, tend to miss appointments and are referred at lower eGFR. Reasons underpinning these associations should be identified to facilitate efforts for targeting this at-risk population, ensuring kidney health for all.